2020
DOI: 10.1177/0192513x20950786
|View full text |Cite
|
Sign up to set email alerts
|

“A Blessing and a Curse” Couples Dealing with Ambivalence Concerning Grandparental Involvement During the Transition to Parenthood—A Longitudinal Study

Abstract: This contribution provides an investigation of first-time parents’ experiences and strategies in dealing with ambivalence—i.e., the simultaneous presence of contradictory emotions—regarding grandparental involvement during the transition to parenthood. The study is based on qualitative longitudinal case studies comprising in-depth individual interviews with 11 Austrian couples of first-time mothers and fathers prebirth, and six months and two years after childbirth ( n = 66 interviews). Parents reported ambiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…However, a few months later this behavioral pattern disappeared, and it was not observed in grandmothers. Since parents may often experience the simultaneous presence of contradictory emotions regarding grandmother's involvement (Zartler et al., 2021 ), during the earlier stage of coparenting it might be difficult for mothers to develop effective strategies to deal with these ambivalent feelings. An alternative interpretation might be that in those families in which coparenting behaviors occur at high frequency both supportive and undermining interactions may be observed at elevated levels and consequently become positively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few months later this behavioral pattern disappeared, and it was not observed in grandmothers. Since parents may often experience the simultaneous presence of contradictory emotions regarding grandmother's involvement (Zartler et al., 2021 ), during the earlier stage of coparenting it might be difficult for mothers to develop effective strategies to deal with these ambivalent feelings. An alternative interpretation might be that in those families in which coparenting behaviors occur at high frequency both supportive and undermining interactions may be observed at elevated levels and consequently become positively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, these disagreements occurred between the parents and the grandparents of the child, and most of the time, the couples were too much dependent on their families; there was no restructuring and readjustment with the original families. Numerous couples with this problem stated that they had excessively unplanned and unrestricted relations with the families of origin due to the wife's employment or proximity of their place of residence to the family of origin (Zartler, Schmidt, Schadler, Rieder & Richter, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…6 Grandmothers were identified as the main support of pregnant women, providing them with information, guidance and emotional support. 11,12 Grandmothers are the ones who have the role of preserving cultural traditions related to this period, they are repositories of knowledge about local medicine and decision-makers in health-seeking behaviors, that is, they decide where childbirth takes place and the need to resort to health services. 11 In a study conducted in an African country, Namibia, 13 three domains were identified in which grandmothers contribute, namely: a) learning to be mothers, through representations of care and examples, as well as information; b) support in breastfeeding; and c) health and well-being in the postnatal period.…”
Section: Grandparents As a Source Of Supportmentioning
confidence: 99%
“…Ambivalent feelings arise when the involvement of grandparents in one or more domains, whether affective, cognitive or behavioral, does not correspond to the wishes and expectations of parents. 12 This ambivalence also exists when there are divergent views of parents and grandparents in relation to concepts and convictions about pregnancy, education, childcare, nutrition, or other fundamental aspects in raising children. In the same study, these ambivalent feelings also occurred when grandparents questioned the roles and attitudes of parents and there were critical judgments of grandparents about their parenting abilities.…”
Section: The Ambivalence Of Feelingsmentioning
confidence: 99%
See 1 more Smart Citation